Production and diagnosis of Vitamin B12 from Lactobacillus reuteri LBIQ1 and its application as a therapeutic food supplement: Produksi dan diagnosis Vitamin B12 dari Lactobacillus reuteri LBIQ1 dan aplikasinya sebagai suplemen makanan terapeutik - Mohammed, Abdulmutalib Abdulla (Indonesian Journal on Health Science and Medicine, 2025)
Vitamin B12 is an essential biological nutrient with multifaceted roles in human physiology and the diet is the main source of it because the human body cannot synthesize it. The photo stability nature of vitamin B12 is a major challenge, as its stability is affected by exposure to light in various industries. Absorption of VB12 also needs to be mediated by internal gastrointestinal factors, and abnormalities of the stomach or lack of such factors result in impaired absorption of VB12. Innovative strategies are therefore required to maintain its stability, effectiveness and ease of absorption, as the current strategies are generally very expensive and are still in the development stage. Thus, The objectives of the current study are to produce and test the therapeutic efficacy of the vitamin in a dietary supplement to the yogurt product, to help increase its intestinal absorption and enhance its optical stability, which can be produced in a formula with a balanced cost. Methods: VB12 was produced in the fermented medium of Lactobacillus reuteri LBIQ1 isolate and then extracted and diagnosed using infrared spectroscopy with the standard vitamin before being added to a laboratory yogurt product and subjected to sensory evaluation to be applied as a therapeutic dietary supplement to a group of skin eczema patients and followed up for three months for exploring its therapeutic effects. Results: Vitamin B12 was successfully produced and extracted from the fermentation medium of the bacterial isolate. The infrared absorption spectrum also demonstrated a high similarity between the extracted and standard samples. Sensory evaluation showed no significant difference between the vitamin-fortified yogurt product and the unfortified control product. The results of applying the fortified product to patients, during the treatment period, proved its effect in reducing the symptoms of skin infections by ≤ 25% in the first month, and (50-75%) in the second month , and (75-100%) at the end of the third month, which gives the possibility that the product has significantly enhanced the intestinal absorption of vitamin B12 and led to stabilization and increased effectiveness (P ≤ 0.05). Conclusion: The preparation and production of vitamin B12 in a fortification yogurt supplement can increase its stability and intestinal absorption and enhance its therapeutic effectiveness as a simple and inexpensive method that can be adopted for commercial and pharmaceutical manufacture. Highlights: Production: VB12 was fermented, extracted, and added to yogurt. Efficacy: Improved stability, absorption, and reduced eczema symptoms significantly. Application: Affordable supplement for commercial and pharmaceutical use. Keywords: Vitamin B12 ; Lactobacillus reuteri LBIQ1 ; Therapeutic food supplement.